Repeat Victimization Among Intimate Partner Violence Victims: The Impact of Guardianship. (April 2018) - Hayes, Brittany E.
Despite progress in the application of routine activity theory to violence against women, much remains unknown about guardianship. The current study examined if presence of a capable adult guardian limited the risk of revictimization by an intimate partner, controlling for social support ( N = 497). Analyses tested differential impacts of guardians by examining if the presence of the victim's friends/family, abuser's friends/family, and/or bystander during the earliest reported physical abuse incident or threat of abuse affected likelihood of revictimization within a year. Odds of revictimization decreased by 60% when the earliest reported physical abuse incident or threat of abuse occurred in the presence of the respondent's friends/family. Implications for practices and research suggestions are discussed.